Project Organizations and Their Present and Preferred Culture - SZABO, Lajos; CSEPREGI, Anikó (Management Dynamics in the Knowledge Economy, 2015)
Although several research has investigated organizational culture (Schein, 2010; Alvesson, 2013), less research has been conducted on the comparison of present and preferred cultures in project context. This paper aims to fill this gap by focusing on project managers and on the investigation of the present and the preferred culture profile of their project organizations. Based on Cameron and Quinn’s (2011) Competing Values Framework using the Organizational Culture Assessment Instrument a quantitative survey was conducted. The questionnaire used gathered data from project managers working in various industries and organizations. The sample consisted of 695 respondents. The empirical study by focusing on project organizations hypothesizes that four project organization groups can be revealed based on their dominant cultural orientation. To test this hypothesis cluster analysis was used. The study also hypothesizes that the present and preferred culture profiles of project organizations do not show significant difference. To prove this statement paired samples t-test was chosen. The results showed that instead of four groups of project organizations with one dominant culture type, there are only three project organizations with the domination of one culture type. Continuing the investigation with these three project organizations, the present and preferred project culture profiles were compared. The results showed that in all three project organizations there are differences between the present and preferred project culture profiles. These differences are manifested mainly by the change of the dominant culture type but the remaining culture types determining the culture profile of the project organizations also show differences.